PRAKTIK KEPEMIMPINAN KEPALA MADRASAH DALAM MENGELOLA PROGRAM PENINGKATAN KOMPETENSI GURU NON-LINEAR DI ERA KURIKULUM MERDEKA DI SMK HAMPAR BAIDURI KALIANDA TAHUN AJARAN 2025/2026 - Deby Mayhelen (UNISAN JURNAL, 2025)
This study aims to describe the leadership practices of the school principal in managing competency development programs for non-linear teachers during the implementation of the Merdeka Curriculum at SMK Hampar Baiduri Kalianda in the 2025/2026 academic year. This research employed a qualitative case study approach. Data were collected through in-depth interviews, observations of training and supervision sessions, and documentation analysis, including lesson plans, training reports, and supervision records. The data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the principal implemented several leadership strategies, including mapping teacher needs, designing internal training based on vocational competencies, facilitating professional learning communities, and establishing partnerships with industries to strengthen teachers’ technical knowledge. The principal also applied academic supervision based on coaching and reflective dialogue to enhance the pedagogical skills of non-linear teachers. In addition to technical support, the principal provided emotional support, motivation, and appreciation to increase teacher confidence. Challenges identified in the implementation include limited practice facilities, varying baseline competencies among teachers, and the complexity of the Merdeka Curriculum. However, these challenges were addressed through adaptive leadership strategies and flexible policy adjustments. Overall, the study concludes that the principal’s leadership practices play a crucial role in improving the competence of non-linear teachers and supporting the successful implementation of the Merdeka Curriculum at the school.